Nuclear magnetic resonance characterization of shallow marine sediments from the Nankai Trough, Integrated Ocean Drilling Program Expedition 333. Issue 4 (9th April 2014) - Daigle, Hugh; Thomas, Brittney; Rowe, Harry; Nieto, Michael
Abstract We measured nuclear magnetic resonance (NMR) relaxation times on samples from Integrated Ocean Drilling Program Expedition 333 Sites C0011, C0012, and C0018. We compared our results to permeability, grain size, and specific surface measurements, pore size distributions from mercury injection capillary pressure, and mineralogy from X‐ray fluorescence. We found that permeability could be predicted from NMR measurements by including grain size and specific surface to quantify pore networks and that grain size is the most important factor in relating NMR response to permeability. Samples within zones of anomalously high porosity from Sites C0011 and C0012 were found to have different NMR‐permeability relationships than samples from outside these zones, suggesting that the porosity anomaly is related to a fundamental difference in pore structure. We additionally estimated the size of paramagnetic sites that cause proton relaxation and found that in most of our samples, paramagnetic material is present mainly as discrete, clay‐sized grains. This distribution of paramagnetic material may cause pronounced heterogeneity in NMR properties at the pore scale that is not accounted for in most NMR interpretation techniques. Our results provide important insight into the microstructure of marine sediments in the Nankai Trough.